Primary Care SHOPping intervention for cardiovascular disease prevention (PC-SHOP): protocol for a randomised controlled trial to reduce saturated fat intake. - Piernas, C; Tsiountsioura, M; Astbury, N; Madigan, C; Aveyard, P; Jebb, S (BMJ Publishing Group, 2019)
Introduction A diet high in saturated fat (SFA) increases the risk of cardiovascular disease (CVD) and intakes in the UK exceed dietary recommendations. The Primary Care Shopping Intervention for Cardiovascular Disease Prevention (PC-SHOP) study aims to test the effect of an intervention for people with raised low-density lipoprotein (LDL) cholesterol involving health professional (HP) advice alone, or in combination with personalised feedback based on nutritional analysis of grocery store loyalty card data, on SFA intake and blood lipids in comparison with no intervention. Methods and analysis PC-SHOP is a three-arm parallel randomised controlled trial with an allocation ratio of 1:3:3 (‘no intervention’: n=16, ‘brief support’: n=48, ‘brief support plus shopping feedback’: n=48, respectively). Participants with raised LDL will be recruited from general practitioner (GP) practices for a 3-month intervention period. In brief support, an HP will deliver a behaviourally informed 10 min consultation and provide a written self-help guide to inform and motivate people to reduce their SFA intake. In brief support plus shopping feedback, the participants will receive the same HP-led behavioural support and, based on data from their grocery store loyalty card, personalised feedback on the SFA content of their grocery shopping, identifying high SFA purchases and suggesting swaps to similar but lower SFA items. Measurements for the primary and secondary outcomes will be collected at baseline and at follow-up (3 months). The primary outcome measure will be the between-group difference in the reduction of SFA intake between baseline and follow-up. Secondary outcomes include changes in blood lipids and SFA content of food purchases, with process measures to consider the feasibility and acceptability of the intervention. Ethics and dissemination This study has been reviewed and approved by the National Health Service Health Research Authority Research Ethics Committee (Ref: 17/SC/0168). The trial findings will be disseminated to academic and HPs through presentations at meetings and peer-reviewed journals and to the public through the media. If the intervention is effective, the results will be communicated to relevant stakeholders, including policymakers and retailers. Trial registration number ISRCTN14279335; Pre-results.